Acidithiobacillia class members originating at sites within the Pacific Ring of Fire and other tectonically active locations and description of the novel genus ‘Igneacidithiobacillus’ - Arisan, Dilanaz; Moya-Beltrán, Ana; Rojas-Villalobos, Camila; Issotta, Francisco; Castro, Matías; Ulloa, Ricardo; Chiacchiarini, Patricia A.; Díez, Beatriz; Martín, Alberto J. M.; Ñancucheo, Iván; Giaveno, Alejandra; Johnson, D. Barrie; et al. (Frontiers in Microbiology, 2024)
Recent studies have expanded the genomic contours of the Acidithiobacillia class, highlighting important lacunae in our comprehension of the phylogenetic space occupied by certain lineages of the class. One such lineage is 'Igneacidithiobacillus', a novel genus-level taxon, represented by 'Igneacidithiobacillus copahuensis' VAN18-1 T as its type species, along with two other uncultivated metagenome-assembled genomes (MAGs) originating from geothermally active sites across the Pacific Ring of Fire. In this study, we investigate the genetic and genomic diversity, and the distribution patterns of several uncharacterized Acidithiobacillia-class strains and sequence clones, ascribed to the same 16S rRNA gene sequence clade. By digging deeper into this data and contributing novel MAGs emerging from environmental studies in tectonically active locations, the description of this novel genus has been consolidated. Using stateof-the-art genomic taxonomy methods, we add to already recognized taxa, an additional four novel Candidate (Ca.) species, including 'Ca. Igneacidithiobacillus chanchocoensis' (mCHCt20-1 TS ), 'Igneacidithiobacillus siniensis' (S30A2 T ), 'Ca.Igneacidithiobacillus taupoensis' (TVZ-G3 TS ), and 'Ca. Igneacidithiobacillus waiarikiensis' (TVZ-G4 TS ). Analysis of published data on the isolation, enrichment, cultivation, and preliminary microbiological characterization of several of these unassigned or misassigned strains, along with the type species of the genus, plus the recoverable environmental data from metagenomic studies, allowed us to identify these taxa´s habitat preferences. Commonalities and lineage-specific adaptations of the seven species of the genus were derived from pangenome analysis and comparative genomic metabolic reconstruction. Findings emerging from this study lay the groundwork for further research on the ecology, evolution and biotechnological potential of the novel genus 'Igneacidithiobacillus'.